Associations between body mass index and hormonal receptor, HER2/neu receptor, as well as other clinical characteristics of breast cancer - Ahmed Qassim Hadi; Adil S. Aqabi (Romanian Medical Journal)
Background. Obesity is a growing problem in the world. Correlations have been found between increasing body mass index (BMI) and breast cancer (BC). BC has multiple predictive and prognostic factors like hormonal receptors, human epidermal growth factor 2 receptor, stage of the disease and grade. Obesity may be differentially related to the risk of different subtypes given the various potential mechanisms underlying its association with breast cancer. The study aims to analyze the association between BMI, BC histopathologic, ER, PR and HER2/neu receptors expression, tumor size axillary nodes involvement, metastasis and nuclear grade. Methods. A cross sectional study was conducted involving 256 cases with breast cancer. Oncology teaching hospital based BC cases had been interviewed and data collected regarding weight and height, estrogen and progesterone receptors status, human epidermal growth factor 2 receptor, stage of the disease, grade of tumor at time of diagnosis, and categorize the cases to pre and postmenopausal state and then subdivided according to body mass index (normal, overweight, obese) and compared between three groups. Results. Overweight / obese people showed a significant statistical effect with estrogen and progesterone receptors, positive p value = 0.026, 0.007 respectively, larger tumor size, p value =0.035, and more lymph node involvement, p-value =0.031 in post-menopausal women, while premenopausal cases did not show significant statistical effect regarding the above-mentioned variables. Body mass index difference did not show a significant statistical effect on human epidermal growth factor 2 receptor, metastasis at diagnosis, tumor grade in both pre and postmenopausal cases. Conclusion. Body mass index difference affects postmenopausal BC cases rather than premenopausal as overweight / obese cases presented with more estrogen and progesterone receptors positive, larger tumor size and more lymph node involvement.